Use of antibiotics and other treatments in Chinese adults with acute cough: An online survey - Xiao-Yang Hu; Ru-Yu Xia; Michael Moore; Beth Stuart; Ling-Zi Wen; Bertrand Graz; Lily Lai; Jian-Ping Liu; Yu-Tong Fei; Merlin Willcox (Integrative Medicine Research)
Background: Acute respiratory tract infections are common worldwide and there has been a rapid increase in antibiotic consumption. This study aimed to identify use of various treatments and their association with the use of antibiotics and patient reported clinical recovery in Chinese adults with acute cough. Methods: An online survey recruiting people who had recently experienced cough was conducted. Their sociodemographic, clinical characteristics, treatments received and their perceived changes in symptoms were collected. Factors influencing avoidance of antibiotics and improvement in symptoms were explored. Results: A total of 22,787 adults with recent acute cough completed the questionnaire, covering all 34 province-level administrative units in China. Most respondents were male (68.0%), young (89.4%, aged 18–45), educated to university/degree or postgraduate level (44.6%), with a median cough severity of 6/10 on a numerical rating scale. Nearly half of the participants (46.4%) reported using antibiotics, among which 93.1% were for presumed upper respiratory tract infections (URTIs). Pharmacies (48.8%) were the most common source of antibiotics. Fewer patients took antibiotics after taking CHM (14.9%), compared to those who started with home remedies (18.0%), or allopathic non-antibiotic medication (25.0%). Antibiotics, allopathic non-antibiotic medications, CHM and home remedies were all perceived beneficial in relieving cough. Conclusions: Chinese adult responders report use of a considerable variety of treatments alone or in combination for acute cough. Patient-reported clinical recovery was similar regardless of treatment. There is likely a high proportion of inappropriate use of antibiotics for treatment of simple acute cough. As the majority of respondents did not use antibiotics as a first-line, and use of CHM was associated with relief of cough symptoms and reduction in the use of antibiotics, this presents an important opportunity for prudent antibiotic stewardship in China.